Orbital Cellulitis Secondary To Spheno Ethmoidalsinusitis Complicating Septic Thrombosis Of Right Superior Ophthalmic Vein And Anterior Cavernous Sinus: A Case Report (International Journal of Scientific Research and Management (IJSRM), 2015)
Superior ophthalmic vein thrombosis is rare entity in present antibiotic era. It can be a harbinger of cavernous sinus thrombosis. In its early presentation CST can masquerade as most commonly seen orbital cellulitis.A male patient presented to us with signs of orbital cellulitis who showed improvement with antibiotics except for abduction limitation and headache.MRI showed thrombosis of superior ophthalmic vein and anterior cavernous sinus.After anticoagulant therapy patient recovered.If CST is undetected early on and prompt treatment not given it can lead to life threatening and sight threatening complications.